Morphological variation and heritability studies of Lagenaria siceraria landraces from northern KwaZulu-Natal, South Africa - LUNGELO GIVEN BUTHELEZI; SYDNEY MAVENGAHAMA; NONTUTHUKO ROSEMARY NTULI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract: Lagenaria siceraria (Molina) Standley belongs to the Cucurbitaceae family. Its nutritious tender shoots, fruits, and seeds are widely consumed in rural communities as leafy vegetables. However, studies on variation and heritability of its agronomic traits are lacking. This study aimed to characterise variability and heritability among L. siceraria genotypes with various fruit and seed morphology from different origins. Seedling, vegetative and reproductive traits were compared among landraces. Landraces varied significantly in their seedling, vegetative and reproductive traits. Significant positive correlations were mainly recorded among reproductive traits. The first five informative principal components had a total variability of 74.393%. Biplot and dendrogram grouped landraces mainly according to fruit and seed morphology and then their origin. In a biplot, Cluster-I grouped landraces with pear-shaped (KSP, RSP, RRP) and curvilinear-shaped (NqRC) fruits. Cluster-II mainly associated landraces with smooth and curvilinear-shaped fruits (KSC, NqSC, NSRC, NSC, MSC and DSI) from different origins. Cluster- III associated landraces with rough textured fruits from the same origin (NRB and NRC). High heritability estimate was recorded among fruit and seed traits. This was the first comprehensive variability and heritability study in the country and therefore it formed basis for available L. siceraria germplasm essential for future breeding programs.